Analisa Pengaruh Berat Isi Pasir Terhadap Daya Dukung Pondasi Dangkal Berbentuk Segitiga dan Lingkaran - Salimah, Serly (Jurnal Mahasiswa Teknik, 2016)
This experiment was conducted to determine the effect of soil bulk density of sand used in the foundation of a circle with a length of sides - sides 11.30 cm and 15.20 cm for a triangular foundation which has the same cross-sectional area of 100 cm2 for a strong increase soil bearing sand.Model foundation of sand placed on the soil surface using a wooden box measuring 100 cm x 100 cm x 100 cm are first filled with sand layer by layer with a bulk density of sand soil is ï§ = 1.3890 gr / cm3 with a height of 20 cm without falling sand sieve, ï§ = 1.4570 kg / cm3 with a height of 20 cm fell in the sand with a sieve number 10, ï§ = 1.5033 kg / cm3 with a height of fall of 30 cm without sieve, ï§ = 1.7090 kg / cm3 with a height of fall 30 using sieve number 10, .ï§ = 1.8128 kg / cm3 with a height of fall of 50 cm without using sieve, ï§ = 1.906 kg / cm3 by using a sieve number 10 from the calculation of the carrying capacity of the foundation obtained the highest with a height of fall of 50 cm using a sieve number 10 . given Terzaghi and method of carrying press Vesic.Then know which interpretation is calculated by graphical methods, namely Methods Chin.These trials were conducted and the conclusions obtained calculate the weight of the content also determines the carrying capacity of the foundation as well as the bulk density of sandy soil.